Peran Perguruan Tinggi Keagamaan Islam Negeri dalam Pengembangan BUMDES Menuju Kemandirian Desa di Provinsi Lampung - Ahmad Hazas Syarif; Ahmad Habibi (ITB AAS INDONESIA Surakarta, 2022)
Higher education plays an essential function and role in the development of Human Resources (HR), this is what makes Indonesians look forward to higher education institutions, especially Islamic colleges, to build skilled and self-sufficient generations. The State Islamic Universities in Lampung is divided into two different institutions, Raden Intan State Islamic University Lampung (UIN RIL) and Metro State Islamic Institute (IAIN Metro) Lampung. Education occupies a strategic position in economic development when high-quality human resources are viewed as the determining factor in successful development. Likewise, most economists agree that human resources are the most decisive factor in character and National development speeds and Economy. This research is a qualitative study, with an entire population of Bumdes in the Lampung province of 1,988 and the identification of samples to 95 BUMDes. The results of this study found that out of 475 BUMDes administrators, there were still a few who had a undergraduate education background (S1), and they are not from state Islamic religious universities, because the contribution of alumni from UIN Raden Intan Lampung and IAIN Jurai Siwo remain limited in the business or partners of the various provinces of Lampung province. Keywords: State Islamic Religious Universities, BUMDes, Independent Villages.